A practical validation study of a commercial accelerometer using good and poor sleepers. Issue 2 (November 2016) - Dickinson, David L; Cazier, Joseph; Cech, Thomas
We validated a Fitbit sleep tracking device against typical research-use actigraphy across four nights on 38 young adults. Fitbit devices overestimated sleep and were less sensitive to differences compared to the Actiwatch, but nevertheless captured 88 (poor sleepers) to 98 percent (good sleepers) of Actiwatch estimated sleep time changes. Bland–Altman analysis shows that the average difference between device measurements can be sizable. We therefore do not recommend the Fitbit device when accurate point estimates are important. However, when qualitative impacts are of interest (e.g. the effect of an intervention), then the Fitbit device should at least correctly identify the effect's sign.